The Consumers’ perceptive of Internet-of-Things: Exploring Users’ Acceptance and Purchase Behavior - Huang, HuiHsin (Discoveries in Agriculture and Food Sciences, 2019)
This paper stands on customer’s view of point to discuss the usage on Internet of Things(IoT). A purchase behavior modelofIoT is constructed based onChaCha model to explore the impact factors that influence customer’s adoption of IoT. The characteristics of IoT itself and customer individualcharacteristics are also included. Then a survey data will be conducted to estimate the parameters of the proposed model. These empirical data are also used to make model calibration. Finally, the application of IoT in marketing management will be present in the conclusion.